Lameness in cattle-A review - Singh, G R; Amarpal, Amarpal; Aithal, H P; Kinjavdekar, P (The Indian Journal of Animal Sciences, 2005)
Lameness in cattle has considerable economical and animal welfare implication .The important causes of lamenass in cattle include laminitis and other foot disorders, arthritis, fractures and affections of tendons and ligaments. Laminitis is one of the leading causes of lameness in cattle. The disease has multifactorial origin but its pathogenesis is still obscure. Improving housing, management, nutritional practices and supplementation of trace elements, minerals and biotin may reduce the incidence of laminitis. Sole ulcers, foot rot, PDD, vertical fissures, interdigital hyperplasia, horizontal fissures, and white line disease are the other important foot affections responsible for lameness. Arthritis may be either infectious or non-infectious (degenerative joint disease) in nature. Treatment of infectious arthritis includes parented or intraarticular administration of antibiotics, joint drainage, and joint lavage by mild antiseptics and replacement of infected synovia with healthy fluid, intraarticular DMSO. The management of DJD is generally unproductive. However, NSAID's allotransplatation of synovia, intraarticular hyaluronidase and low levels of ultrasound and diathermy have been found to have some beneficial effects. Traction at the time of dystocia, stamping by the dam and fall are the major causes of fracture in young calves. However, vehicular accidents, fall and fight with other animals contribute to most of the fractures in adult animals. The factors like type of fracture, the age and weight of the animal, the temperament of the animal, post- operative management of the patients and selection of appropriate techniques dictate the success of fracture management in cattle. Nevertheless, fractures in young animals and adult cattle below 250 kg of body weight can be managed with a reasonably good success rate. Contractures and injuries to the tendons of the digital flaxor, gastrocnemius and peroneus tertius muscles are commonly encountered in bovines. Different types of suturing techniques, grafts and implants and measures to prevent peritendinous adhesions have been used successfully for the repair of tendon injuries. Most of the knowledge available on lamencss especially due to foot disorders in cattle is derived from the work done in Europe and America and very little infomation is available on indigenous cattle. Studies should, therefore, be conducted on indigenous cattle to correctly judge the losses to the farmers on account of lameness in cattle and to suggest suitable remedial measures.